The Best Trading System to Generate Profits - F. K., H.; Noor Azlinna, Azizan (2011)
This research attempts to use risk adjusted performance measure sucha as Jensen and Sharpe to evaluate the profitability of technical trading systems in the Malaysian stock market. We tested 13 techical trading systems such 1-30 dual simple moving average crossover, 5-20 dual simple moving average crossover, 3-7 exponental moving average crossover, relative strength index (RSI), momentum, stochastic, moving average converge divergence (MACD), five Channel Breakout Systems (CBO 20-20, CBO 20-5, CBO 10-5 and CBO 15-5) and the directional movement index (DMI). The finding reveal that 8 out of 13 trading systems produced significally positive gross returns when 0.44 percent transaction cost is applied. This finding confirms that technical analysis not only produce investment returns but also can be used as risk management as its ability to reduce risk and also confirm the random walk hypothesis for the market tested.